Early History of Educational Dictionaries and the First Bilingual Dictionaries - Nashirova Shakhnoza Burievna (Zien Journals, 2023)
It is based on the fact that the bilingual dictionary, compiled in order to serve the correct understanding, originated in the form of manuals – educational dictionaries. In particular, the bilingual glossaries found in the temple library in Nippur, dating back to four millennia BC, intended for communication between two completely different tribes -Sumerian and Akkadian Semites who lived in Ancient Mesopotamia – were the first appearance of modern bilingual educational dictionaries.
Keywords: Dictionary; educational dictionaries